RESEARCH ON THE EVOLUTION OF THEORETICAL IDEAS ABOUT THE ARCHITECTONICS OF THE INTERNATIONAL ECONOMY - Vandina, Olga; Mukuchyan, Razmon; Rozanov, Dmitry; Prokhorova, Elena; Cherkassky, Petr (Revista Inclusiones, 2020)
International economic integration involves the convergence of the economies of neighboring countries into a single economic complex based on deep and stable economic relations between enterprises. Regionalization is largely predetermined by objective processes of the world economy. Discussion. The general pattern of regionalization is the progressive nature and sequence of development of integration processes from the lower to the upper strata. Results. Regionalization of the world economy is the dominant global economic trend, including world-class force majeure.